The Correlation of I'jaz Bayani with Scientific Signals in the Story of Maryam: A Study of the Miracles of Language and Science in the Qur'an - Nurhayat, Tasya Putri; Fathurrohman, Asep Ahmad; Zulaiha, Eni (International Journal of Nusantara Islam, 2025)
This research aims to study the correlation between i’jaz bayani and scientific hints in the story of Maryam in the Qur’an. Using a language and science approach, this research analyzes the choice of diction, sentence structure, and word use in Surah Maryam, which shows the miracle of the language of the Qur'an. The main focus of this study is the use of the word "rutab" (wet dates), which is scientifically proven to have great benefits for pregnant and giving-birth women. This finding shows that the meaning contained in this choice of words is not only linguistically beautiful but also in accordance with modern medical facts. This shows that there is a close relationship between i’jaz bayani and scientific signals in the Al-Qur'an, as well as being a protest against orientalist accusations that doubt the miracles of the stories in the Al-Qur'an.